Fictions of Authority : Women Writers and Narrative Voice - Lanser, Susan Sniader, 1944- (Book collections on Project MUSE., 1992)
Drawing on narratological and feminist theory, Susan Sniader Lanser explores patterns of narration in a wide range of novels by women of England, France, and the United States from the 1740s to the present. She sheds light on the history of "voice" as a narrative strategy and as a means of attaining social power. She considers the dynamics in personal voice in authors such as Mary Shelley, Charlotte Brontë, Zora Neale Hurston, and Jamaica Kincaid. In writers who attempt a "communal voice"--Including Mary Wollstonecraft, Elizabeth Gaskell, Joan Chase, and Monique Wittig--she finds innovative strategies that challenge the conventions of Western narrative